Physicochemical Characterization of the Quality of Groundwater: Case Study of the Tebessa Plain (North-East Algeria) - Ghrieb, Lassaad; Maoui, Ammar; Boudjebieur, Essia; Gueroui, Yacine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In order to characterize the physicochemical quality of groundwater, and to examine the behavior of factors influencing water chemism in the Tebessa Plain, which is part of a semi-arid region located in the northeast of Algeria, physicochemical analyses were carried out on 32 water samples from the Mio-Plio quaternary water table.
Keywords: groundwater quality; physicochemical quality; semi-arid region; gypsiferous formations; Tebessa Plain; North-East Algeria; wody gruntowe; jakość wód gruntowych; region półpustynny; formacje gipsowe; Algieria północno-wschodnia